Real Time Battery Monitoring Control in Mini Generating System - Nursusanto, Usman; Khairunnisa', Khairunnisa'; Hartoyo, Hartoyo (DPTE FT UNY, 2022)
ABSTRACTMini-generating systems such as PLTS utilize batteries as energy storage media. The increasing use of PLTS also adds to the problem of battery waste (B3). The battery monitoring tool is used to monitor the condition of PLTS batteries and used batteries. This research was conducted using the ADDIE method. Data collection techniques were carried out through literature study, observation, and practice. Research products are battery packs and BMS boxes. The error rate of BMS readings on the values of voltage, current, and temperature are 4.59%, 2.002% and 0.83%. The undervoltage reading error rate is 0.3V. The BMS protection circuit can break the stacking battery circuit when a battery-related problem occurs. The first experiment obtained a measured voltage value of 11.5V when it was not connected to the charging input and the discharging load. The second experiment obtained a measured charging voltage of 12.2V and a measured discharging voltage of 11.9V. Based on these results it can be concluded that the battery is in good condition.ABSTRAKSistem mini pembangkit seperti PLTS memanfaatkan baterai sebagai media penyimpanan energi. Pemanfaatan PLTS yang semakin meningkat juga menambah permasalahan limbah baterai (B3). Alat monitoring baterai digunakan untuk memantau kondisi baterai PLTS maupun baterai bekas. Penelitian ini dilaksanakan dengan metode ADDIE. Teknik pengumpulan data dilakukan melalui studi literatur, observasi dan praktik. Produk penelitian berupa baterai pack dan box BMS. Tingkat kesalahan pembacaan BMS terhadap nilai tegangan, arus, dan suhu yaitu 4,59%, 2,002% dan 0,83%. Tingkat kesalahan pembacaan undervoltage sebesar 0.3V. Rangkaian proteksi BMS dapat memutus rangkaian baterai susun saat terjadi permasalahan terkait baterai. Percobaan pertama diperoleh nilai tegangan terukur 11.5V ketika tanpa disambungkan ke input charging dan beban discharging. Percobaan kedua diperoleh tegangan charging terukur 12.2V dan pada tegangan discharging terukur 11.9V. Berdasarkan hasil tersebut dapat disimpulkan bahwa baterai dalam kondisi baik.